西Dronning Maud LandのFimbul Ice Shelfに点在するアイスライズの地形、現在の質量収支、過去の変動 - 松岡, 健一; Joel, Brown; Elisabeth, Isaksson; Jack, Kohler; Reinhard, Drews; Carlos, Martin; Frank, Pattyn; Kenichi, Matsuoka (2013)
Ice rises, local ice caps on elevated ocean beds surrounded by ice shelves, impact the stability of the surrounding ice shelf and nearby outlet glaciers which, in turn, control the mass balance of the Antarctic Ice Sheet. In 2011, we started to investigate three ice rises in the vicinity of the Fimbul Ice Shelf, western Dronning Maud Land (DML), East Antarctica. Fimbul Ice Shelf is fed by Jutulstraumen outlet glacier that accounts for about 10% of the total outgoing mass from the DML sector of the Antarctic Ice Sheet. This mass flux is as large as that of Shirase and West Ragnhild Glaciers, two other most significant glaciers in DML. Our major findings include 1) low elevations of the ice-rise beds (100-350 m b.s.l.), 2) presence of englacial stacked upward arches in (Raymond Bumps) near the current ice-flow divides, 3) varying ice shelf thickness and surface velocity at the grounding zones on opposite sides of the ice rises, 4) orthographically influenced surface mass balance patterns, and 5) asymmetric surface flow speeds over the ice-flow divides. We use Results #4 and #5 to investigate recent (decadal) mass balance of the ice rises. Also, present-day thickness changes and ice rheology will be determined with repeated FM-CW radar measurements in the vicinity of the flow divides. These rheology estimates and Results #2, 3, 4, and 5 will be used to constrain thermo-mechanically coupled ice-flow models to examine timing of divide-flow onset, thinning/thickening rates (i.e. mass balance) of the ice rises and effects of changes of ice-shelf thicknesses at the end of the local flow fields on the ice-flow divide positions. 第4回極域科学シンポジウム 個別セッション：[OM] 気水圏 11月15日（金） 統計数理研究所 ３階セミナー室１（D305） conference object